Case Study : The Impact of Blended Learning on Students' English Writing Skills - Leonny Raicella Sumbayak; Anggraini Thesisia Saragih; Christine Helena Natalia (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This case study investigates the impact of blended learning on students' English writing skills, focusing on a group of third-semester students majoring in English Education. Blended learning, which combines traditional face-to-face instruction with online learning components, is explored as a pedagogical approach that enhances writing proficiency through increased engagement and personalized feedback. Data were collected through questionnaires administered to 20 participants, revealing that a significant majority of students perceive blended learning as a motivating factor that fosters their writing development. The findings indicate that this approach not only improves grammar and overall writing skills but also provides ample opportunities for practice and constructive feedback, which are essential for skill enhancement. Additionally, the study highlights the importance of a supportive learning environment that encourages collaboration and community among students. The results advocate for the broader implementation of blended learning strategies in English writing instruction, emphasizing their potential to empower students and improve their language acquisition outcomes. This research contributes to the growing body of literature on effective teaching methodologies in language education and underscores the need for continuous adaptation and innovation in instructional practices.